Giant pre-sacral neurofibroma. Issue 795 (January 1992) - Agarwal, M.; Azzopardi, A.; Mufti, G. R.
Abstract : We report a case of pre-sacral neurofibroma diagnosed on a routine medical examination. The pathological features and management criteria of these rare tumours are discussed.